The Intersection Between Normative and Empirical: Madhhab Orientation in Marriage and Divorce Law in Indonesia - Fatawi, Fatawi; Usman, Suparman; Hidayat, Ahmad; Tarihoran, Naf’an (International Journal of Nusantara Islam, 2024)
The codification of Islamic law (taqnīn) is crucial in providing legal certainty in marriage and divorce in Indonesia while maintaining the relevance of sharī’ah values amidst social changes. This study aims to examine the implementation of Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI) in the context of madhhab pluralism. The research employs a qualitative descriptive method with normative and empirical analysis approaches. The findings reveal that the codification of Islamic law faces challenges in accommodating diverse fiqh perspectives, ensuring gender justice, and addressing the administrative needs of society. The maqāṣid al-sharī‘ah approach is an essential foundation for an inclusive transformation of Islamic law, particularly in aligning classical fiqh values with modern legal norms. This study recommends harmonizing Islamic law principles with the national legal system to create just, relevant, and beneficial regulations for Indonesian society